BOTANIC URBANISM: The Technopolitics of Controlled Environments in Singapore's Gardens by the Bay. (24th November 2021) - McNeill, Donald
Abstract: This article examines the development of Singapore's Gardens by the Bay, a parkland and botanical gardens complex on a reclaimed land platform which opened in 2012. It provides three readings of the development based on different types of technopolitical governance. First, it discusses the significance of the location of the Gardens on one of Singapore's reclaimed land platforms, part of the 'terraforming' strategies of the government's land development process. Second, it situates the project within the state's complex botanical relationship with colonial and postcolonial knowledge circuits, and suggests that this is part of the governance challenge of 'acclimatizing' to the tropical climate. Third, it suggests that the Gardens are part of an 'exhibitionary complex' based on engaging publics with the state's ability to harness science to provide a controlled, ordered polity. To illustrate this, the article brings together the political discourse of two Singaporean prime ministers with a discussion of the architectural design and environmental engineering of the project, and the curatorial practices of the state's National Parks Board. The article demonstrates the complex interplay of environmental, architectural and botanical engineering with state strategies of both citizen engagement and tourist attraction, and the importance of the practice of exhibition within urban megaprojects.